Roads to Prosperity? Assessing the Link Between Public Capital and Productivity - Fernald, John G (American Economic Review, 1999)
Does the positive correlation between infrastructure and productivity reflect causation? If so, in which direction? I find that when growth in roads (the largest component of infrastructure) changes, productivity growth changes disproportionately in U.S. industries with more vehicles. That vehicle-intensive industries benefit more from road-building suggests that roads are productive. At the margin, however, road investments do not appear unusually productive. Intuitively, the interstate system was highly productive, but a second one would not be. Road-building thus explains much of the productivity slowdown through a one-time, unrepeatable productivity boost in the 1950's and 1960's. (JEL E62, O47, R53)